Behaviour of reinforced concrete beam under dynamic loading / Sharul Azman Shamsuddin (Faculty of Civil Engineering, 1997)
The increase in use of High Strength Concrete (HSC) in modem construction is tremendously high. Thus its behaviour need to be understood clearly . The behaviour of High Strength Concrete beam (RC beam) under dynamic loading with respect to the serviceability and ultimate limits had been studied. Four numbers of High Strength Concrete (HSC) beams of size 125 mm x 150mm x 1400 mm had been casted with four nos . longitunal reinforcement ( bottom 2T16 and top 2R6 ) together with R6 stirrup at 80 mm c/c spacing . One of the beam is loadedwith static loading conditions and tested until failure in order to achieve the yield strength of the beam . For testing under dynamic load , two number of beams was tested under repeated load with 50% maximum and 30% min (mean load 40%) of yield load (110.405 kN ). A Sinusoidal wave pattern were used with 3 million cycles and 9 million cycles . Parameter investigate include . deflection , crack pattern and ultimate load .